Kompleksnyj podchod v ocenke funkcional'nogo sostojanija professional'nych sportsmenov - Guba, V. P.; Marinich, V. V. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2014)
In article the functional condition of highly skilled players in mini-soccer (futsal) is analysed, the integrated approach to the solution of this problem is developed, recommendations for effective preparation are offered.